Self and parasite-derived peptides selected upon DERAA-bearing HLA-DRB1 alleles activate CD4+ T cells from Chagas cardiomyopathy patients and are associated with ventricular dysfunction - Souza-Silva, Thaiany G.; Neves, Eula G. A.; Teixeira-Carvalho, Andrea; Figueiredo, Amanda Braga; Morais, Katia Luciano Pereira; Apostólico, Juliana; Rodrigues, Hélcio; Kalil, Jorge; Juliano, Maria Aparecida; Juliano, Luiz; Araújo, Silvana Silva; Pantaleao, Alexandre Negrão; et al. (Frontiers in Immunology, 2025)
IntroductionHuman infection with the protozoan Trypanosoma cruzi causes Chagas disease, which may lead to a deadly dilated cardiomyopathy resulting from T-cell-mediated inflammation. We found that specific HLA-DRB1 alleles (*0103, *0402, *1301, and *1302) that display the DERAA motif are linked to this severe clinical manifestation of Chagas disease.MethodsWe employed computational analysis, in vitro functional assays, and single-cell RNA sequencing to determine the response of CD4+ T cells from indeterminate (IND) and cardiac (CCC) Chagas patients to peptides selected on DERAA-bearing alleles.ResultsWe observed that these alleles display binding affinity towards host-derived peptides with sequence similarity to parasite-derived proteins. These peptides can activate and induce proliferation of CD4+ T-cells from CCC, but not IND. Importantly, the magnitude of this response correlated with the severity of ventricular dysfunction and increased production of soluble factors associated with myocardial fibrosis. Analysis of differentially expressed genes (DEGs) in activated CD4+ T-cells from individuals with the DERAA-DRB1 alleles demonstrated a high expression of cytotoxic, chemotactic and proapoptotic genes, linking these cells with pathogenic functions. Finally, we observed the upregulation of genes that code for the host proteins that contain the potentially pathogenic peptides in the cardiac tissue of CCC, suggesting their involvement in cardiomyopathy.DiscussionOur findings highlight the ability of CD4+ T-cells from CCC patients to recognize and react to foreign and self-peptides, thereby emphasizing the importance of HLA-DRB1 alleles in the presentation of potentially pathogenic antigens and in the amplification of CCC pathology.